PRODUCTION EFFICIENCY OF PIPIL CORN FARMINGIN THE LIMA PULUH KOTA REGENCY, WEST SUMATRA: EFISIENSI PRODUKSI USAHA TANI JAGUNG PIPILDI KABUPATEN LIMA PULUH KOTA SUMATERA BARAT - Ramadhan, Fajri (ROCE : Jurnal Pertanian Terapan, 2024)
The study aims to determine the technical application of pipil corn cultivation in Lima Puluh Kota Regency, analyze pipil corn farming in Lima Puluh Kota Regency, and analyze the level of production efficiency (technical, allocative, and economic) of pipil corn in Lima Puluh Kota Regency.  Lima Puluh Kota Regency, West Sumatra Province with research locations, namely: Nagari Bukik Sikumpa, Nagari Guguak VIII Koto, and Nagari Sungai Talang. The determination of the research location was taken into consideration. The Nagari was chosen with the criteria of the Nagari with the largest production and the largest harvest area. The results of the analysis show that the application of cultivation techniques in Pipil corn farming such as seed preparation, land cultivation, planting, fertilization, maintenance, and harvesting in Lima Puluh Kota Regency is not by the recommended cultivation techniques with a suitability value of 63.5% percent. Farmers who are technically efficient amount to 9 percent, with technical efficiency values ranging from 0.916 - 1.000 with an average value of 0.961, indicating that technical efficiency is not too problematic in pipil maize farming in Lima Puluh Kota Regency because the average value for technical efficiency is close to 1. Who are technically efficient farmers have used inputs efficiently, so that they can produce optimum production.  Economically efficient farmers amounted to 9 percent, with economic efficiency values ranging from 0.946 - 1.000 with an average value of 0.982, which means that most Lima Puluh Kota farmers are not economically efficient.